Yarn to go - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Yarn retreat mysteries., 2013)
When she inherits her aunt's yarn retreat business, dessert chef Casey Feldstein decides to host a scheduled retreat, even though she knows nothing about knitting, and she investigates when a retreat regular is murdered.